More Liveable” Speculations: the Gender of SF in Margaret Atwood’s Short Story “Oursonette” and in the Comic Book / Graphic Novel War Bears - Ostalska, Katarzyna (Zagadnienia Rodzajów Literackich, 2020)
Taking into account the broadness of the SF genre, the article commences with examining the difference between speculative fiction and science fiction, as outlined specifically by Donna J. Haraway and Margaret Atwood. Drawing on Atwood’s understanding of speculative genre, the paper analyses two separate but intertwined artistic forms: a classic short story with embedded dialogue and a comic book / graphic novel based upon the extended version of the earlier narrative. The short story “Oursonette” was written by Atwood as a part of a national project of artists commemorating the sesquicentennial anniversary of the Canadian Confederation. It depicts Victory in Europe Day, 8 May 1945, from the perspective of Canada and its impact upon the publishing of “Canadian whites,” otherwise known as WECA comic books. Partially black-and white War Bears (2019), referring to the tradition of “Canadian whites” comics, is a modern graphic novel, co-authored with Ken Steacy, which essentially uses the plot of Atwood’s “Oursonette” as the foundation for drawing an expanded story that precedes and follows the original. The narrative is not simply elaborated, a new dimension of visual imagery and a significant layer of intersectionality have changed its meaning to a large extent. The article analyses those alterations in detail to come to a conclusion as to whether they are beneficial or redundant to the original form and content. Thematically, the paper probes the gendered dimension of Atwood’s (and partly Steacy’s) rendering of the superheroine subcategory, with regard to SF genre and its literary convention. The article compares how this issue is represented in both examined literary genres: a narrative by Atwood and a comic book / graphic novel by Atwood and Steacy.